Survey of disease awareness, treatment behavior and treatment satisfaction in patients with atopic dermatitis in Korea: A multicenter study. Issue 10 (18th July 2018) - Jung, Hye Jung; Bae, Joo Youn; Kim, Jung Eun; Na, Chan Ho; Park, Gyeong Hun; Bae, You In; Shin, Min Kyung; Lee, Young Bok; Lee, Un Ha; Jang, Yong Hyun; Han, Tae Young; Ahn, Ji Young
Abstract: In Korea, there is a high dependency on oriental medicine and folk remedies ( Korean J Asthma Allergy Clin Immunol, 25, 2005, 110). In addition, inaccurate information available through the Internet is increasing ( Korean J Dermatol, 44, 2006, 137). So, there is always a possibility that patients may have difficulty obtaining accurate information about atopic dermatitis (AD). The aim was to determine the awareness, treatment behavior and treatment satisfaction of patients with AD and their caregivers. In October 2017, patients diagnosed with AD at nine hospitals were enrolled in this study. A questionnaire was completed by each patient. A total of 371 subjects were surveyed. In response to the question asking about knowledge of AD, the correct answer rate was 55.4%. Bathing using soap, body scrub and moisturizer showed favorable outcomes. A total of 54.9% patients responded that they were reluctant to use steroid ointment. When asked about their previous treatment, 39.6% reported using oriental medicine and 26.5% had tried folk remedies. The hospital treatment satisfaction score was 6.6. Patients usually applied their knowledge in their daily lives. However, there was a lot of inaccurate knowledge. Therefore, it is important for patients to understand the characteristics of this disease and obtain correct information.